DESIGNING AN ENVIRONMENTAL INFORMATION MANAGEMENT SYSTEM (EIMS): THE CASE OF WEB MAPPING PORTAL FOR FARMERS - Wahyudi Agustiono (Jurnal Ilmiah Kursor, 2014)
Today concerns for environmental sustainability practices are getting lots of attention due to the regulatory requirements, market pressure and natural resources deterioration. While many businesses have responded these demands by incorporating sustainable thinking into their strategies, in the same vein, researchers have attempted to provide different ground in understanding environmental sustainability best practices. IS researchers is no exception due to the growing recognition that the ICT and IS as being part of the solution to the environmental sustainability problem. This study, therefore, addresses this call by presenting the results of longitudinal and indepth investigation of an IS design for supporting environmental information management and referred as Environmental Information Management System (EIMS). To better understand how a new EIMS can be designed, it then considers the design of a new Web Mapping Portal to assist farmers in land management and monitoring as a fruitful empirical context of investigation. Overall, the findings of this study show the value of IS scholars going beyond the dominant research on IS designed for supporting business (e.g. ERP, SCM and ERP) into more emerging research stream by addressing research question on how can IS be designed to address the complex problem in environmental sustainability.